Emotional and Communicative Competence of Students of Higher Medical Institutions - Obloberdiyevna, Djamaldinova Shakhlo (Journal of Research in Innovative Teaching and Inclusive Learning, 2023)
Relevance of the topic. The development of emotional and communicative competence is of decisive importance for students of higher medical educational institutions. Effective communication is essential in healthcare as it enables healthcare professionals to establish a good relationship with patients and provide them with the best possible care. Emotional competence, on the other hand, helps students understand and manage their emotions, which is important in high-stress healthcare settings. By developing these competencies, students can become better health care providers and provide more compassionate care to their patients.